Familial recurrence risks for multiple sclerosis in Australia. Issue 12 (7th May 2011) - O'Gorman, C; Freeman, S; Taylor, B V; Butzkueven, H; ,; Broadley, S A
Abstract : Background: Genetic susceptibility to multiple sclerosis (MS) has been recognised for many years. Considerable data exist from the northern hemisphere regarding the familial recurrence risks for MS, but there are few data for the southern hemisphere and regions at lower latitude such as Australia. To investigate the interaction between environmental and genetic causative factors in MS, the authors undertook a familial recurrence risk study in three latitudinally distinct regions of Australia. Methods: Immediate and extended family pedigrees have been collected for three cohorts of people with MS in Queensland, Victoria and Tasmania spanning 15° of latitude. Age of onset data from Queensland were utilised to estimate age-adjusted recurrence rates. Results: Recurrence risks in Australia were significantly lower than in studies from northern hemisphere populations. The age-adjusted risk for siblings across Australia was 2.13% compared with 3.5% for the northern hemisphere. A similar pattern was seen for other relatives. The risks to relatives were proportional to the population risks for each site, and hence the sibling recurrence-risk ratio (λs ) was similar across all sites. Discussion: The familial recurrence risk of MS in Australia is lower than in previously reported studies. This is directly related to the lower population prevalence of MS. The overall genetic susceptibility in Australia as measured by the λs is similar to the northern hemisphere, suggesting that the difference in population risk is explained largely by environmental factors rather than by genetic admixture.